Integration versus unilateralism? The political economy of the FTAA. - Romero, Marco (2016)
Romero argues that the FTAA process follows an inexorable path, one that involves the bureaucratic agents of the Latin American economies. Lacking are broad debates about this process and clear assessments of its implications. An analysis of the position of the US government and the Congress shows a clear trend toward unilateralism. According to the author, what is necessary is a profound consideration of the current perspectives, and a new locus on Latin American patterns of integration, which locate trade issues within development policies.